Current perspectives of oncoplastic breast surgery in Pakistan - Lubna Mushtaque Vohra; Dua Jabeen; Danish Ali; Syeda Sakina Abidi; Rizwan Javaid; Sana Zeeshan; Abida Khalil Sattar (Journal of the Pakistan Medical Association, 2022)
Oncoplastic breast surgery is based on the concept of tumour-specific immediate reconstruction. It combines both local and distant techniques to maintain breast texture, symmetry and cosmesis without compromising oncological outcome. The current narrative review was planned to highlight the current state and future of oncoplastic breast surgery in low- and middle-income countries where its utilisation in surgical practice remains insubstantial because majority of the surgeons who are treating breast cancer are either general surgeons or breast surgeons who do not have expertise in oncoplastic breast surgery or reconstructive surgery. Moreover, scarcity of financial resources, ignorance about oncoplastic breast surgery techniques, disfigurement distress and cultural taboos coerce women to hide in the shadows with their breast disease. Oncoplastic breast surgery needs more exposure in a developing country like Pakistan. Continuous...